Impact of Personality Traits on the Academic Achievement of Male and Female Adolescents: A Study of Block Keller of District Shopian (J&K) - Heena Qadir, (Indian Journal of Extension Education, 2014)
The totality of qualities and traits, as of character or behavior, that are peculiar to a specific person constitute personality.The personality of males and females differs considerably due to inherent differences in biological traits that consequentlyaffect other dimensions of their behavior.Their personalities along with specific associated traits get reflected in variousspheres of their lives and perform differently. Like other facets, personalities play a significant role in the learning abilitiesand influence the educational status of males and females. Males and females possess different capabilities to learn onaccount of their inherent differences.Thus, it is in the interest of educational psychology to evaluate different personalitytraits of males and females and the respective impact on their performances in the field of education to utilize theirpotential properly.This will help educationists in general and teachers in particular to come up with promising strategies ofteaching best suited to both the genders. The present study is conducted to investigate the impact of varying personalitytraits on the academic achievement of male and female adolescents. The present study employs descriptive method ofresearch. It was conducted at block Keller of District Shopian in the state of Jammu and Kashmir where from a sample of80 male and female adolescent students was selected through random sampling method from different Government andPrivate schools with equal proportion of gender. The primary research tool administered to the respondents included in theselected sample was the Cattle's High School Personality Questionnaire (HSPQ). The findings of the study reveal that theimpact of different personality traits of male and female adolescents on the academic performance in Mathematics andGeneral Science subjects is significant while as it is insignificant for subjects Urdu, Social Science, English and Value andMoral education.